Język polski jako element tożsamości (na przykładzie wypowiedzi Polaków i Rosjan z obwodu kaliningradzkiego) - Kuszak, Kinga; Sadowska, Katarzyna (Kultura-Społeczeństwo-Edukacja, 2020)
The article discusses the issue of Polish language as an element of identity of Poles and Russians living in Kaliningrad. The authors, during a visit to the University of Immanuel Kant, had the opportunity to do interviews with Poles and Russians living in Kaliningrad, for whom Polishis an important element of identity. The authors divided the respondents into two groups for whom Polish is an element of inherited identity and for whom Polish is an element of identity acquired in the education process. These analyzes precede reflections on the specifics and history ofKaliningr ad and the kaliningrad district.